Needs Analysis for the Development of Interactive Infographic Media Based on Discovery Learning on Renewable Energy Topics in Elementary Education - Marita, Raini; Stiawan, Deris; Raharjo, Makmum (Journal of Innovation and Research in Primary Education, 2025)
The low level of students’ understanding in learning Natural Sciences, particularly on renewable energy topics, in elementary schools is partly due to the lack of interactive learning media that align with children's learning characteristics. This study aims to analyze the needs of both teachers and students for the development of interactive infographic media grounded in the discovery learning approach. A quantitative descriptive method was employed, using closed-ended questionnaires as the primary data collection instrument. The respondents consisted of 30 students and six classroom teachers from an elementary school in Musi Banyuasin Regency. The questionnaire covered pedagogical, technical, cognitive, aesthetic, and evaluation aspects. The findings revealed that the majority of students struggled to comprehend renewable energy concepts in the absence of visual media. Furthermore, 90% of students expressed a preference for learning materials incorporating images, videos, and animations. All teacher respondents emphasized the need for media that supports active and visual learning tailored to the developmental characteristics of elementary students. These findings underscore the urgent need to develop interactive infographic media based on discovery learning to enhance students’ conceptual understanding. Practically, the results serve as a foundation for designing learning tools that are engaging, age-appropriate, and capable of fostering independent exploration in science education at the elementary level.